2000
DOI: 10.1097/00002371-200001000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Shared Melanoma Antigens in Association With Major HLA-A Alleles by Tumor Infiltrating T Lymphocytes From 123 Patients With Melanoma

Abstract: A total of 123 tumor-infiltrating T lymphocyte (TIL) cultures established from patients with HLA-A1, -A2, -A3, -A24, or -A31 metastatic melanoma in the Surgery Branch, National Cancer Institute, were screened for recognition of shared melanoma antigens including five melanosomal proteins (tyrosinase, MART-1/melan-A, gp100, TRP1, TRP2) as well as peptides derived from MAGE-1 and MAGE-3. Examination of the specificity of these T cells indicated that 16% of HLA-A1 TIL, 57% of HLA-A2 TIL, 7% of HLA-A3 TIL, 13% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 32 publications
4
67
0
Order By: Relevance
“…Abundant data indicate that 'shared' melanocyte lineage antigens, such as tyrosinase 38 , can be recognized by T cells in patients with melanoma, particularly following investigational vaccinations [39][40][41] . Larger-scale analyses are needed to understand the full repertoire of shared and tumour-specific epitopes that can be recognized in melanomas, even in untreated patients.…”
Section: Modified Oncolytic Herpes Virusmentioning
confidence: 99%
“…Abundant data indicate that 'shared' melanocyte lineage antigens, such as tyrosinase 38 , can be recognized by T cells in patients with melanoma, particularly following investigational vaccinations [39][40][41] . Larger-scale analyses are needed to understand the full repertoire of shared and tumour-specific epitopes that can be recognized in melanomas, even in untreated patients.…”
Section: Modified Oncolytic Herpes Virusmentioning
confidence: 99%
“…Among this group, many specific antigens were identified, such as NY-ESO-1 and the MAGE-1 antigens, which belong to cancer-testis family, gp100, which belongs to the differentiation antigens group, and many more (Visseren et al, 1997;Chen et al, 1998a, b;Jager et al, 1998;Pascolo et al, 2001). It is well-established that human melanoma cells express antigens that are recognized by cytotoxic T-lymphocyte (CTL) derived from cancer patients (Brichard et al, 1993;Kawakami et al, 1994;Wolfel et al, 1994;Fleischhauer et al, 1996;Pittet et al, 1999;Kawakami et al, 2000;Engelhard et al, 2002;Romero et al, 2002;Schaed et al, 2002). These are mainly differentiation antigens such as gp100, MART1 and tyrosinase, which represent a very attractive target because their expression is limited to a well-defined cell lineage (melanocytes).…”
Section: T-cell Receptor-like Antibodiesmentioning
confidence: 99%
“…Immunity against differentiation Ags is a form of autoimmunity that can mediate destruction of tumors and normal tissues (1)(2)(3)(4)(7)(8)(9)(10)(11). In fact, tumor-infiltrating lymphocytes from patients with melanoma most often recognize melanocyte differentiation Ags (12). Previous studies have shown that xenogeneic immunization against the melanosomal differentiation Ags tyrosinase-related protein-1 TRP-1/gp75 (3,4), dopachrome tautomerase (1), and gp100/pmel 17 (2), either with DNA encoding the Ag or with recombinant protein, can result in the rejection of transplanted syngeneic melanomas in mice.…”
mentioning
confidence: 99%